Plan de negocios para la creación de una empresa de consultoría a través de E-commerce 2.0 en la ciudad de Bogotá, D.C. (2024)
This business plan focused on the development of an e-commerce 2.0 consulting model in Bogotá, integrating Multimodal Generative Artificial Intelligence (MGAI) technologies and “no code” tools that enable its implementation without the need for programming. The proposal aims to reduce friction (cognitive, emotional, and physical) between clients and the company through an application powered by virtual assistants or AI avatars designed to respond empathetically and personally to any type of inquiry on digital devices.